SEGYM: A Novel Electrified Weight Machine for Performing Free-Weight Training - Jangyeon Park; Keeung Yoo; Dongwan Choi; Jungsu Choi (IEEE Access)
As part of digital healthcare, weight equipment has been motorized using electric motors to overcome the limitations of conventional weight equipment that relies on the weight of objects. However, this has been limited to cable and strength machines, and the most popular free weights, which lack safety and ease of use, have not yet been electrified. As such, in this study, SEGYM was developed as electrified weight equipment for free weight training. SEGYM aimed to imitate the load and motion characteristics of traditional free weights while achieving consistent human-robot interaction. The actuating modules, located on both sides of SEGYM, generate loads independent of user motion through a belt-drive mechanism, similar to gravitational loads. Additionally, the barbell module, combined with the actuating modules, applies ergonomic design to enable natural human movement in three-dimensional space while delivering the load. To implement the same resistance sensation as conventional free weights, a multi-layered disturbance rejection controller (MDRC), based on robust control, was applied to the actuating modules. This controller changes the dynamic characteristics of SEGYM to match those of traditional free weights. An experiment with elite weightlifters was conducted to verify the similarity between SEGYM and conventional free weights. The results confirmed their similarity.